Culturally responsive approaches to evaluation empirical implications for theory and practice - Chouinard, Jill Anne (Los Angeles SAGE, 2020)
Evaluators have always worked in diverse communities, and the programs they evaluate are designed to address often intractable socio-political and economic issues. Evaluations that explicitly aim to be more responsive to culture and cultural context are, however, a more recent phenomenon. This book utilizes a conceptual framework that foregrounds culture in social inquiry and then uses that framework to analyze empirical studies across three distinct cultural domains of evaluation practice (Western, Indigenous and international development). The authors provide a comparative analysis of these studies and discuss lessons drawn from them in order to help evaluators extend their current thinking and practice. They conclude with an agenda for ongoing research in culturally responsive approaches in evaluation."--Provided by publisher.
Introduction -- A conceptual framework for inquiry -- Methodology and descriptive overview of selected studies -- The indigenous context -- The Western/Northern American context -- The international development context -- A discussion of the conceptual framework across domains of practice -- Concluding thoughts.
Includes bibliographical references (pages 139-161) and index.
Keywords: Evaluation Research -- Social Action Programs; Culture